Lessons from the Successes and Failures of Anglo-American Protestant Christian Medical Missionaries in China from the 1840s to the 1950s - NI Lidong, (Journal of Research for Christianity in China (JRCC), 2025)
From the perspective of salvation, this topic reviews the impact of the loss of the 1840s-to-1950s medical ministries delivered by British and American Protestant missionaries on the healthcare sector in China so as to find the root of doctor-patient conflicts and the decaying medical ethic in order to find the way of solving the fundamental problem. The scholarly value of this paper lies in the inspiration that helps the decision-making officials and relevant scholars to observe the same history event from different visions and to seek the second explanation in the light. Understanding the root of conflicts among human beings is the key to form a harmonious society and a peaceful world.